2014
DOI: 10.5114/ms.2014.45428
|View full text |Cite
|
Sign up to set email alerts
|

Ceragenins – a new weapon to fight multidrug resistant bacterial infections

Abstract: Growing antibiotic resistance among pathogenic microorganisms is one of the most challenging problems. Often, a single mutation in a bacterial cell leads to the formation of a new drug resistance mechanism. The ceragenins are a novel class of antibiotic, offering great promise in future treatment of infections. These cationic antimicrobial lipids are net positively charged cholic acid derivates that are electrostatically attracted to the negatively charged membranes of bacteria, certain viruses, fungi, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Active-release coatings containing ceragenins are attractive because of the bactericidal properties of ceragenins, their activity against established biofilms, their stability in the presence of proteases and other enzymes, and the ease by which they can be manipulated [4,20,83]. Williams et al [99] characterized physical and chemical properties of a coating containing CSA-13 as a novel active release agent in a medical grade polymer coating on fracture fixation plates.…”
Section: Medical Device Coatings Containing Cerageninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active-release coatings containing ceragenins are attractive because of the bactericidal properties of ceragenins, their activity against established biofilms, their stability in the presence of proteases and other enzymes, and the ease by which they can be manipulated [4,20,83]. Williams et al [99] characterized physical and chemical properties of a coating containing CSA-13 as a novel active release agent in a medical grade polymer coating on fracture fixation plates.…”
Section: Medical Device Coatings Containing Cerageninsmentioning
confidence: 99%
“…As a result, substantial effort is being expended to develop new therapeutics and mechanisms for controlling microbial growth to avoid entering a "post-antibiotic" era in which commonly used antibiotics are no longer effective in treating infections [2,3]. For example, according to the U.S. Center for Disease Control and Prevention (CDC), each year more than two million people in the United States are infected by drugresistant bacteria, and a substantial portion of those infections are caused by multidrug-resistant bacteria [4].…”
Section: Introductionmentioning
confidence: 99%
“…11 Modified antimicrobial LL-37 peptides, such as FF/CAP18, and a synthetic antimicrobial peptide mimic, ceragenin CSA-13, also have the potential to suppress growth of colon cancer cells. [12][13][14][15] It was found that expression of LL-37 is reduced during progression of stomach cancer from atrophic gastritis to adenocarcinoma. The modified antimicrobial peptide FF/CAP18 exerts antiproliferative effects on the SAS-H1 squamous carcinoma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if such mechanisms fail, bacteria trapped in DNA/F-actin networks undergo extensive changes of gene expression leading to the development of bacterial biofilm. Interestingly, the formation of bundles induced by F-actin, DNA or bacteriophages is diminished for synthetic analogues of CAPs, such as ceragenins, which maintain their high antibacterial activity despite the presence of PE at the infection site [46,47]. Importantly, elevated eDNA and NET levels and their accumulation in biological fluids is a factor activating innate immune responses, which considerably affect the development of such diseases as asthma and chronic obstructive pulmonary disease [48], periodontitis [49], antineutrophil cytoplasmic antibody-associated vasculitis (AAV) [29], or cancerassociated thrombosis [50].…”
Section: Condensation Of Dna By Cationic Peptidesmentioning
confidence: 99%